Development of SWOT Method with Additional Elements of Aspirations and Results in Music Industry - Kanggep Andrijana Kusuma (Universitas Pasundan, 2021)
The development of strategies to win the music industry business competition is growing and is becoming one of the most important and a mainstay in companies engaged in the music industry in planning strategies for achieving organizational goals both now and in the future. From that thought, the authors combined the well-known SWOT methodology with several complementary elements which are expected to make this method more effective in analyzing and providing valuable inputs for the progress of a music industry. We hereby include the elements of Aspiration and result taken from the SOAR methodology to be combined with the SWOT design so that it is hoped that it will become a method that can provide better results. Keywords: SWOT, SOAR, Analytical, Business, Method, Planning, Strategic Planning,